2011
DOI: 10.1590/s1516-89132011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome among Kaingang native americans in southern Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…Both aimed to verify the prevalence of metabolic syndrome, using SBP 130mmHg and DBP 85mmHg to identify HBP (suggestive of a clinical diagnosis of arterial hypertension). These cutoff points were different than the ones we used here 28,29 . The first study included 82 adults and showed a 24.2% HBP rate in men and 28.6% in women 29 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Both aimed to verify the prevalence of metabolic syndrome, using SBP 130mmHg and DBP 85mmHg to identify HBP (suggestive of a clinical diagnosis of arterial hypertension). These cutoff points were different than the ones we used here 28,29 . The first study included 82 adults and showed a 24.2% HBP rate in men and 28.6% in women 29 .…”
Section: Discussionmentioning
confidence: 88%
“…High prevalence rates of excess weight have also been found in indigenous peoples in Brazil 5,11,27,28,31 . The highest HBP and the highest mean SBP and DBP were in overweight or obese individuals, although this difference was only statistically significant in men.…”
Section: Discussionmentioning
confidence: 98%
“…One study (19) evaluated hypertension compared to the two cutoff points mentioned above. It is noteworthy that one study (30) established the largest cutoff as higher than or equal to 130/85 mmHg, and one study (10) showed no diagnostic criteria. It is also noteworthy that in seven studies (11,23,(26)(27)(28)30,33) , the presence of previous diagnosis of hypertension and/or treatment with antihypertensive medication were considered in addition to blood pressure levels.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…Mercury column 08 (11)(12)18,(21)(22)24,29,30) Aneroid 05 (13,(19)(20)26,33) Mercury column and/ or Aneroid 02 (10,25) Random-Zero 04 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)23,27) Semi-automatic 04 (28,(31)(32)34) Procedures prior measuring blood pressure…”
Section: Equipment Used For Measurementsmentioning
confidence: 99%
See 1 more Smart Citation